Ethical consumption in the digital age: Analyzing benefit types, temporal distance, and normative factors for Gen Z - Jay R. Fraser; Moosung Chung; Hongsik John Cheon (Global Business & Finance Review (GBFR), 2023)
Purpose: This study investigates which message appeals more effectively induce consumers' ethical consumption by using combinations of self- or other-benefit appeals with future or present benefits and determines whether priming personal norms or social norms influences the effect. Design/methodology/approach: To test the theoretically derived priori hypotheses concerning the role of benefit, temporal distance, norms, and ethical consumption message, this research presented three experiments (two-Way ANOVA). The first test showed no difference in ethical consumption between the self- and other-benefit appeal types. The second experiment tested the hypothesis that self-benefit and other-benefit appeals are more effective for present and future benefits, respectively. The final experiment assessed whether self-benefit and other-benefit appeals primed with personal and social norms, respectively, would be more effective. Findings: Our results suggest that the appeal approach should be combined with either social or personal norms when the benefit is received to create more effective marketing messages when advertising ethical goods. Research limitations/implications: Owing to the growing trend in ethical consumption, we are becoming more concerned about animal welfare and seeking ethical meat options. Originality/value: This study promotes environmental sustainability, demonstrating that Method Products manufactures goods utilizing eco-friendly materials.
Keywords: 650; Ethical consumption; Cultural difference; Social norms; Temporal distance